The Association Between Timing of Routine Preoperative Blood Testing and a Composite of 30-Day Postoperative Morbidity and Mortality. (October 2018) - Ruetzler, Kurt; Lin, Peirong; You, Jing; Schacham, Yehoshua; Naylor, Amanda J.; Sessler, Daniel I.; Saager, Leif
Abstract : BACKGROUND: Laboratory testing is a common component of preanesthesia evaluation and is designed to identify medical abnormalities that might otherwise remain undetected. While blood testing might optimally be performed shortly before surgery, it is often done earlier for practical reasons. We tested the hypothesis that longer periods between preoperative laboratory testing and surgery are associated with increased odds of having a composite of 30-day morbidity and mortality. METHODS: We obtained preoperative data from 2, 320, 920 patients in the American College of Surgeons National Surgical Quality Improvement Program who were treated between 2005 and 2012. Our analysis was restricted to relatively healthy patients with American Society of Anesthesiology physical status I–II who had elective surgery and normal blood test results (n = 235, 010). The primary relationship of interest was the odds of 30-day morbidity and mortality as a function of delay between preoperative testing and surgery. A multivariable logistic regression model was used for the 10 pairwise comparisons among the 5 laboratory timing groups (laboratory blood tests within 1 week of surgery; 1–2 weeks; 2–4 weeks; 1–2 months; and 2–3 months) on 30-day morbidity, adjusting for any imbalanced baseline covariables and type of surgery. RESULTS: A total of 4082 patients (1.74%) had at least one of the component morbidities or died within 30-days after surgery. The observed incidence (unadjusted) was 1.7% when the most recent laboratory blood tests measured within 1 week of surgery, 1.7% when it was within 1–2 weeks, 1.8% when it was within 2–4 weeks, 1.7% when it was between 1 and 2 months, and 2.0% for patients with most recent laboratory blood tests measured 2–3 months before surgery. None of the values within 2 months differed significantly: estimated odds ratios for patients within blood tested within 1 week were 1.00 (99.5% confidence interval, 0.89–1.12) as compared to 1–2 weeks, 0.88 (0.77–1.00) for 2–4 weeks, and 0.95 (0.79–1.14) for 1–2 months, respectively. The estimated odds ratio comparing 1–2 weeks to each of 2–4 weeks and 1–2 months were 0.88 (0.76–1.03) and 0.95 (0.78–1.16), respectively. Blood testing 2–3 months before surgery was associated with increased odds of outcome compared to patients whose most recent test was within 1 week ( P = .002) and 1–2 weeks of the date of surgery. CONCLUSIONS: In American Society of Anesthesiologists physical status I and II patients, risk of 30-day morbidity and mortality was not different with blood testing up to 2 months before surgery, suggesting that it is unnecessary to retest patients shortly before surgery.